Luteal Phase Support Using Subcutaneous Progesterone: A Systematic Review - Conforti, Alessandro; Carbone, Luigi; Iorio, Giuseppe Gabriele; Cariati, Federica; Bagnulo, Francesca; Marrone, Vincenzo; Strina, Ida; Alviggi, Carlo (Frontiers in Reproductive Health, 2021)
Luteal phase support (LPS) is crucial in assisted reproductive technology (ART) cycles when the luteal phase has been found to be defective. Such deficiency is most likely related to the supraphysiological steroid levels that usually occurr in stimulated cycles which, in turn, could severely affect luteinizing hormone (LH) secretion and function, thereby negatively influencing the luteal phase. A number of different medications and routes have been successfully used for LPS in ART. Although an optimal protocol has not yet been identified, the existing plethora of medications offer the opportunity to personalize LPS according to individual needs. Subcutaneous administration progesterone has been proposed for LPS and could represent an alternative to a vaginal and intramuscular route. The aim of the present systematic review is to summarize the evidence found in the literature concerning the application of subcutaneous progesterone in ARTs, highlighting the benefits and limits of this novel strategy. With this aim in mind, we carried out systematic research in the Medline, ISI Web of Knowledge, and Embase databases from their inception through to November 2020. Randomized controlled trials (RCTs) were preferred by the authors in the elaboration of this article, although case-control and cohort studies have also been considered. According to our findings, evidence exists which supports that, in women with a good prognosis undergoing a fresh in vitro fertilization (IVF) cycle, subcutaneous Pg is not inferior to vaginal products. In the Frozen-thawed embryo transfer (FET) cycle, data concerning efficacy is mixed with an increased miscarriage rate in women undergoing a subcutaneous route in oocyte donor recipients. Data concerning the acceptance of the subcutaneous route versus the vaginal route are encouraging despite the different scales and questionnaires which were used. In addition, a cost-effective analysis has not yet been conducted.